High-Grade Prostate Cancer: Favorable Results in the Modern Era Regardless of Initial Treatment. (31st January 2012) - Ramahi, Emma H.; Swanson, Gregory P.; Jackson, Matthew W.; Du, Fei; Basler, Joseph W.
Abstract : Purpose . We performed a retrospective study to determine the outcome of a modern cohort of patients with high-grade (Gleason score ≥ 8) prostate cancer treated with radical prostatectomy, radiation therapy, or hormone therapy. Methods . We identified 404 patients in the South Texas Veteran's Healthcare System Tumor Registry diagnosed with high grade prostate cancer between 1998 and 2008. Mean follow-up was4.62 ± 2.61 years. End points were biochemical failure-free survival, overall survival, metastasis-free survival, and cancer-specific survival. Results . 5-year overall survival for patients undergoing radical prostatectomy, radiation therapy, and hormone therapy was 88.9%, 76.3%, and 58.9%, respectively. 5-year metastasis-free survival for patients undergoing radical prostatectomy, radiation therapy, and hormone therapy was 96.8%, 96.6%, and 88.4%, respectively, and 5-year cancer-specific survival was 97.2%, 100%, and 89.9%, respectively. Patients with a Gleason score of 10 and pretreatment prostate-specific antigen > 20 ng/mL had decreased 5-year biochemical failure-free and cancer-specific survival. Patients with a pretreatment prostate-specific antigen > 20 ng/mL had decreased 5-year overall survival. Discussion . Even for patients with high-grade disease, the outcome is not as dire in the modern era regardless of primary treatment modality chosen. While there is room for improvement, we should not have a nihilistic impression of how these patients will respond to treatment.